2014
DOI: 10.1111/jipb.12158
|View full text |Cite
|
Sign up to set email alerts
|

BnWRI1 coordinates fatty acid biosynthesis and photosynthesis pathways during oil accumulation in rapeseed

Abstract: Photosynthesis in "green" seeds, such as rapeseed, soybean, and Arabidopsis, plays a substantial role in the improved efficiency of oil accumulation. However, the molecular mechanism underpinning the coordinated expression of fatty acid (FA) biosynthesis- and photosynthesis-related genes in such developing seeds remains to be elucidated. Here, we found that seed-specific overexpression of BnWRI1, a WRI1 homolog from rapeseed (Brassica napus cv. ZGY2), results in enhanced chlorophyll content in developing seeds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 43 publications
5
66
0
Order By: Relevance
“…3). Similar results were also obtained in transgenic Arabidopsis and rapeseed overexpressing BnWRI1 (Liu et al 2010;Wu et al 2014). Although the molecular mechanisms underlying the enhanced growth of embryonic cells in the transgenic lines overexpressing WRI1 are still unclear, a higher ratio of sucrose to hexose is known to be related with cell expansion and seed filling at the later stage of seed development (Weber et al 1996(Weber et al , 1997.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…3). Similar results were also obtained in transgenic Arabidopsis and rapeseed overexpressing BnWRI1 (Liu et al 2010;Wu et al 2014). Although the molecular mechanisms underlying the enhanced growth of embryonic cells in the transgenic lines overexpressing WRI1 are still unclear, a higher ratio of sucrose to hexose is known to be related with cell expansion and seed filling at the later stage of seed development (Weber et al 1996(Weber et al , 1997.…”
Section: Discussionsupporting
confidence: 81%
“…It was observed that the levels of seed oils increased by approximately 10-20 % in T 4 seeds of transgenic Arabidopsis overexpressing AtWRI1 (Cernac and Benning 2004). When rapeseed WRI1 (BnWRI1) was overexpressed in Arabidopsis and rapeseed, the total seed oil contents increased by approximately 20 and 10 %, respectively, and in particular, the size of seed oil bodies was observed to be enlarged in rapeseed overexpressing BnWRI1 (Liu et al 2010;Wu et al 2014). In addition, the overexpression of maize WRI1 (ZmWRI1) caused an increase in the contents of kernel oil in transgenic maize plants by approximately 31 % (Shen et al 2010;Pouvreau et al 2011).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Arabidopsis is only a model species and has not been subjected to artificial selection for agronomic traits such as seed oil content or yield. However, WRI1 and DGAT1 overexpression have been reported individually to boost seed oil content in maize (Zheng et al, 2008;Shen et al, 2010) and oilseed rape (Brassica napus; Weselake et al, 2008;Wu et al, 2014). Furthermore, suppression of SDP1 can also enhance seed oil content in oilseed rape (Kelly et al, 2013a) and Jatropha curcas (Kim et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…WRINKLED1 (WRI1) was shown to be an essential transcription factor for TAG synthesis in many species, and its overexpression led to 10-30% increase in seed oil content in arabidopsis, rapeseed and even maize (Cernac and Benning, 2004;Baud et al, 2007;Liu et al, 2010;Pouvreau et al, 2011;Wu et al, 2014). Overexpression of arabidopsis AtWRI1 in camelina seeds led to an increase in seed weight and seed size, and as expected, to 8-31% increase in seed oil content (An and Suh, 2015).…”
Section: Improving Camelina Oil Yieldmentioning
confidence: 99%